Advice from retired secondary school principals in Ireland on how to lead as a principal (Journal of Applied Learning and Teaching, 2024)
At the core of this paper is a report on a study aimed at generating theory about the perspectives of recently retired secondary school principals in Ireland (n=15) on how beginning secondary principals in the nation should lead. The hope from the outset was that the result could be drawn upon to offer supporting insights to providers, including university-led programmes, so as to inform the pre-service and ongoing preparation of aspiring and appointed principals. What follows is presented in four parts. First, an exposition is provided on the rationale that informed that aim. Secondly, recent developments in relation to school leadership in Ireland are considered. Thirdly, details on the conduct of the study are presented. Fourthly, the study results are outlined.